Academic Service Quality Management For The Quality Of First High School Graduates (Case Study Of SMPN 1 Kresek And SMPN 1 Mauk) - Gunawan, Endra; Sauri, Sofyan; Hanafiah, Hanafiah; Koswara, Nandang (CV. Inara, 2022)
One of the causes of the low quality of education graduates in Indonesia is the low quality management of academic services in schools, especially in State Junior High Schools. The low quality of graduates in junior high schools is due to common mistakes made by principals in managing education so that the quality of junior high schoolgraduates is low, including: (1) principals lead with a weak vision and mission; (2) the principal as a leader who lacks innovation in educational programs; (3) Principals lead without utilizing technology in the learning process; (4) Principals lead by ignoring social networks; (5) The principal does not provide creative space for teachers and students; (6) The principal does not use conflict as a driver of progress. In this regard, the researchers chose the title of the study, namely